KINEMATIC COMPARISON BETWEEN NATIONAL AND AMATEUR TAEKWONDO ATHLETES IN THE AP HURIGI (AXE KICK - Hidayat, Iwa Ikhwan; Rusdiana, Agus; Haryono, Tono; Kurniawan, Tian; Imanudin, Iman; Umaran, Unun; Syahid, Angga M; Salman, Salman (MEDIKORA, 2024)
Taekwondo is a Korean martial art characterized by rapid kicks. In the combat category, technical ability is the key to success in gaining points. The aphurigi technique (axe kick) is one of the important techniques in taekwondo because the technique gives a point contribution of around 20% in the match. Thus, it is necessary to investigate kinematic analysis to determine the kinematic parameters that contribute to the success of the aphurigi (axe kick) kick technique. 24 athletes were involved in this research, divided into 2 groups, namely the national level group and the regional group. All samples performed aphurigi kicks, then recorded using a camera and analyzed using skill spector software in 2 dimensions. There are 6 parameters analyzed consisting of kick speed, hip position, angular speed, and kick range. From the measurements that have been carried out, the results show that national-level athletes have significant differences compared to regional athletes in kick speed in the upswing phase, p-0.003, hip position, p-0.045, and knee angle in the upswing phase, p-0.026. However, there were no significant differences in other parameters, including kick speed in the upswing phase, kick range, and knee angle in the upswing phase. The results show the importance of a specific training program to train kinematic parameters that can influence aphurigi kick performance, therefore amateur athletes can master effective kick techniques and compete at the national level.